Extraction of 3D trajectories of mandibular condyles from 2D real-time MRI - Isaieva, Karyna; Leclère, Justine; Paillart, Guillaume; Drouot, Guillaume; Felblinger, Jacques; Dubernard, Xavier; Vuissoz, Pierre-André (Magma (New York, N.Y.), 2025)
Objective Computing the trajectories of mandibular condyles directly from MRI could provide a comprehensive examination, providing both anatomical and kinematic details. This study aimed to investigate the feasibility of extracting 3D condylar trajectories from 2D real-time MRI. Materials and methods Twenty healthy subjects underwent real-time MRI while performing jaw opening and closing movements. One axial and two sagittal slices were segmented using a U-Net-based algorithm. After motion compensation, the centers of mass of the resulting masks were projected onto the coordinate system based on anatomical markers and temporally adjusted. The quality of the computed trajectories was evaluated using metrics designed to estimate movement reproducibility, head motion, and slice placement symmetry. Results The segmentation of the axial slices demonstrated good-to-excellent quality; however, the segmentation of the sagittal slices required some fine-tuning. On average, the intercuspal position shifted by 0.6 mm after an opening–closing cycle. The difference in the superior–inferior coordinate of the condyles in the intercuspal position was 1.5 mm on average. Some subjects demonstrated a significant discrepancy between the axial and the sagittal trajectories. Discussion Real-time MRI enables the extraction of condylar trajectories for evaluating some clinically relevant parameters. However, attention is required during patient installation and image acquisition.